The Associated Factors of Quality of Life among Stroke Survivors: A Study in Indonesia - Fitria Handayani; Reni Sulung Utami; Chandra Bagus Ropyanto; Niken Safitri Dyan Kusumaningrum; Yuni Dwi Hastuti (Nurse Media Journal of Nursing, 2022)
Background: The prevalence and burden of stroke are still high, especially in low and middle-income countries. Stroke affects the economy and physics related to the Quality of Life (QoL). Various QoL-associated factors, including sociodemographic, functional outcome, emotional, and cognitive function, were studied. However, there was very limited information about the QoL-associated factors among stroke survivors in Semarang, Indonesia.Purpose: This study aimed to identify the QoL-associated factors among stroke survivors in Semarang, Indonesia.Methods: This cross-sectional study was conducted in outpatient services and involved 57 ischemic stroke survivors using convenience sampling. Demographic and clinical information were obtained using medical records and questionnaires. The questionnaires were the Short Version of Specific Stroke Quality of Life (SS-QoL) to measure QoL, GRID-HAMD 17 to measure Post Stroke Depression (PSD), Mini-Mental Status Examination (MMSE) to measure cognitive impairment, Barthel–Index (BI) to measure functional outcome, Hamilton Anxiety Rating Scale (HAM-A) to measure anxiety, and Multidimensional Scale of Perceived Social Support (MSPSS) to measure social support. Linear regression was conducted in the model performance of QoL-associated factors.Results: The stroke duration was 155(18) days, and 50.9% of participants were males. The linear regression showed that age (-.164 95% CI -.412 - .084), marital status (3.937 95% CI 1.010 - 6.864), functional outcome (.127 95% CI .013 - .241), PSD (-1.090 95% CI -2.144 - -.036), cognitive function (.308 95% CI -.482 - 1.098) and anxiety (-.408 95% CI -1.125 - .268) were QoL-predictors (p<.001, adjusted R2=52.1). It is assumed that age, marital status, functional outcome, PSD, cognition, and anxiety significantly predict the QoL among ischemic stroke survivors.Conclusion: The QoL-associated factors were age, marital status, functional outcome, PSD, cognition, and anxiety. These associated factors of QoL should be considered as elements in formulating nursing interventions that aim to improve the good QoL among stroke survivors.